Alcohol-dysregulated miR-30a and miR-934 in head and neck squamous cell carcinoma. Issue 1 (December 2015) - Saad, Maarouf; Kuo, Selena; Rahimy, Elham; Zou, Angela; Korrapati, Avinaash; Rahimy, Mehran; Kim, Elizabeth; Zheng, Hao; Yu, Michael; Wang-Rodriguez, Jessica; Ongkeko, Weg
Abstract Background Alcohol consumption is a well-established risk factor for head and neck squamous cell carcinoma (HNSCC); however, the molecular mechanisms by which alcohol promotes HNSCC pathogenesis and progression remain poorly understood. Our study sought to identify microRNAs that are dysregulated in alcohol-associated HNSCC and investigate their contribution to the malignant phenotype. Method Using RNA-sequencing data from 136 HNSCC patients, we compared the expression levels of 1, 046 microRNAs between drinking and non-drinking cohorts. Dysregulated microRNAs were verified by qRT-PCR in normal oral keratinocytes treated with biologically relevant doses of ethanol and acetaldehyde. The most promising microRNA candidates were investigated for their effects on cellular proliferation and invasion, sensitivity to cisplatin, and expression of cancer stem cell genes. Finally, putative target genes were identified and evaluatedin vitro to further establish roles for these miRNAs in alcohol-associated HNSCC. Results From RNA-sequencing analysis we identified 8 miRNAs to be significantly upregulated in alcohol-associated HNSCCs. qRT-PCR experiments determined that among these candidates, miR-30a andmiR-934 were the most highly upregulatedin vitro by alcohol and acetaldehyde. Overexpression ofmiR-30a andmiR-934 in normal and HNSCC cell lines produced up to a 2-fold increase in cellular proliferation, as well as induction of the anti-apoptotic geneBCL-2 . Upon inhibition of these miRNAs, HNSCC cell lines exhibited increased sensitivity to cisplatin and reduced matrigel invasion. miRNA knockdown also indicated direct targeting of several tumor suppressor genes bymiR-30a andmiR-934 . Conclusions Alcohol induces the dysregulation ofmiR-30a andmiR-934, which may play crucial roles in HNSCC pathogenesis and progression. Future investigation of the alcohol-mediated pathways effecting these transformations will prove valuable for furthering the understanding and treatment of alcohol-associated HNSCC.